Application of video-assisted online interactive learning to improve student mathematics learning outcomes - Surur, Agus Miftakus Surur; Akhyar, Muhammad Khoiril; Ridwanulloh, M.Ubaidillah; Mohamed, Hasna Binta; Günerhan, Hatira (Pusat Studi Pengembangan Pembelajaran Matematika, 2023)
Rapid technological developments should support improving the quality of learning, one of which is online learning. . Online learning is carried out because learning in class is limited by space and time, thus limiting learning interactions. This study aims to describe and analyze student learning outcomes in mathematics by using video-assisted online interactive learning. Classroom Action Research (CAR) is used in this study with some stages namely preparation, action, observation, and reflection. The results of online learning using interactive videos are cycle I on student learning outcomes that obtain scores exceeding the minimum completeness score of 57% and are said to be complete. However, there are still 43% of students who obtain learning outcomes that are less than the minimum standard of completeness or have not been completed. The cause of this is the initial adaptation of students to using media that is packaged interactively. It was continued in the second cycle of learning to produce a learning completeness percentage of 86% for students who had exceeded the minimum standard of mastery scores. This shows an increase from cycle I to cycle II. In cycle II, the process of adaptation and the active participation of students began to have an impact on learning outcomes. Continuing in cycle III shows that the number of students who complete learning reaches 86%, the same as in cycle II, but there are still differences. Cycle II to Cycle III experienced an increase in the average value of learning outcomes, namely cycle II of 76.36; in cycle III, it increased to 78.79. These results indicate that online interactive learning using video can improve student mathematics learning outcomes.